Non-local electron energy probability function in a plasma expanding along a magnetic nozzle - Boswell, Rod W.; Takahashi, Kazunori; Charles, Christine; Kaganovich, Igor D. (Frontiers in Physics, 2015)
Electron energy probability functions (eepfs) have been measured along the axis of low pressure plasma expanding in a magnetic nozzle. The eepf at the maximum magnetic field of the nozzle shows a depleted tail commencing at an energy corresponding to the measured potential drop in the magnetic nozzle. The eepfs measured along the axis demonstrate that the potential and kinetic energies of the electrons are conserved and confirm the non-local collisionless kinetics of the electron dynamics.